TCR Dependent Metabolic Programming Regulates Autocrine IL-4 Production Resulting in Self-Tuning of the CD8+ T Cell Activation Setpoint - Crofts, Kali F.; Holbrook, Beth C.; Soto-Pantoja, David R.; Ornelles, David A.; Alexander-Miller, Martha A. (Frontiers in Immunology, 2020)
The ability of T cells to sense and respond to environmental cues by altering their functional capabilities is critical for a safe and optimally protective immune response. One of the important properties that contributes to this goal is the activation setpoint of the T cell. Here we report a new pathway through which CD8+ T cells can self-tune their activation threshold. We find that in the presence of a strong TCR engagement event, there is a shift in the metabolic programming of the cell where both glycolysis and oxidative phosphorylation are significantly increased. This diverges from the switch to a predominantly glycolytic profile that would be predicted following naïve T cell activation. This altered metabolic program results in the production of autocrine IL-4. Both metabolic pathways are required for this cytokine to be made. IL-4 signaling in the activated CD8+ T cell results in modulation of the sensitivity of the cell, establishing a higher activation setpoint that is maintained over time. Together these data demonstrate a novel mechanism for the regulation of IL-4 production in CD8+ T cells. Further, they reveal a new pathway for the self-tuning of peptide sensitivity. Finally, these studies uncover an unexpected role for oxidative phosphorylation in regulating differentiation in CD8+ T cells.